Konsep Keluarga Sakinah Dalam Kehidupan Bermasyarakat - Subhan, Subhan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to describe and analyze the concept of family in today's social life. This research uses a qualitative approach with the results of interviews and literature studies. The results show that the sakinah family is a family that is fostered by a legal marriage, able to provide affection to family members so that they have a sense of security, peace and happiness. Sakinah in the family can be understood as a state of remaining calm despite facing many obstacles and tests of life. The ideal family is one that is able to maintain peace, and has love and love. A harmonious family or happy family is an atmosphere of harmony, harmony characterized by the presence of good agreement and cooperation between husband and wife, father, mother and parent-child. Which includes the atmosphere in the family, giving attention to each other, the existence of communication, and mutual respect between family members.